The Influence of Product Displays on Purchasing Decisions (Study on Aroma Bakery and Cake Shop Karya Jaya) - Afif, Muhammad Hamdan; Sriyanto, Dharmawan; Siregar, Onan Marakali (CV. Proaksara Global Transeduka, 2024)
Consumer purchasing decisions are the result of choices made by individuals when buying a product. This process involves selecting one solution out of many options, followed by real consequences. A crucial aspect of this decision-making process is the product display. The presentation of goods in a store plays a key role in creating a visual image that influences consumers' perceptions of beauty and the product itself.This study seeks to investigate the impact of product display on purchasing decisions at Aroma Bakery and Cake Shop Karya Jaya. The research methodology employed is quantitative with an associative approach. Data was collected from 96 respondents using the Accidental Sampling technique. Primary data was gathered through questionnaires distributed to consumers who had recently made purchases at Aroma, while secondary data was collected through literature and documentation reviews. The data analysis included validity testing, reliability testing, classical assumption testing, simple linear regression analysis, hypothesis testing, and determination coefficient calculation. Results from the study revealed that the product display significantly affects purchasing decisions. The product display variable had a positive impact on buying decisions, as demonstrated by the t-test results (9.332> 1.6612) and the low significance value (0.000 < 0.05). According to the coefficient of determination test, product displays explained 48% of the variation in purchasing decisions, with external factors accounting for the remaining 52%.The findings underscore the importance of product displays in influencing consumer purchasing decisions at Aroma Bakery and Cake Shop Karya Jaya.